2022
DOI: 10.3389/fnut.2022.802562
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index and Oxygen Therapy Requirement Associated With Longer Hospital Length of Stay in Patients With Moderate to Severe COVID-19: Multicenter Prospective Cohort Analyses

Abstract: PurposeTo evaluate whether the prognostic nutritional index (PNI) is related to the oxygen therapy requirement at hospital admission and to ascertain the prognostic effect of the PNI and the oxygen therapy requirement as predictors of hospital length of stay in patients with moderate to severe coronavirus disease 2019 (COVID-19).MethodsThis is a post-hoc analysis in hospitalized patients with moderate to severe COVID-19. The participants were categorized: (1) non-oxygen therapy (moderate COVID-19 not requiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Of note is the inconsistency in nutrition assessment methods reported ( n = 5), reflecting current guidelines, which do not specifically recommend just one method to quantify malnutrition 11,40 . Rates of malnutrition in this review varied from 31% in patients with COPD 24 to 100% in a population with COVID‐19 20 . Whereas similar rates of malnutrition have been reported in studies recruiting patients with COPD (30% malnourished), 41 other studies have reported much lower rates of malnutrition in those with COVID‐19 (45% malnourished) 42 .…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Of note is the inconsistency in nutrition assessment methods reported ( n = 5), reflecting current guidelines, which do not specifically recommend just one method to quantify malnutrition 11,40 . Rates of malnutrition in this review varied from 31% in patients with COPD 24 to 100% in a population with COVID‐19 20 . Whereas similar rates of malnutrition have been reported in studies recruiting patients with COPD (30% malnourished), 41 other studies have reported much lower rates of malnutrition in those with COVID‐19 (45% malnourished) 42 .…”
Section: Discussionmentioning
confidence: 93%
“…Studies were categorized into the nutrition parameters they reported on (Table 4), with some studies addressing multiple parameters. Five studies reported results related to route of nutrition, 14,17,21,23,24 five on nutrition assessment, 16,18–20,24 two on anthropometry, 18,22 one on quantifying nutrition intake, 24 and one on nutrition screening 15 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations